COMPARİSON OF ALVARADO AND RIPASA SCORES İN PATİENTS WİTH ACUTE APPENDİCİTİS - Esmer Gökçe, Mine; Korkmaz, İlhan; Teki̇n, Yusuf; Yurtbay, Sefa; Demi̇rtaş, Erdal; Özsoy, Orhan; Özbay, Sedat; Kukul Güven, Fatma (Cumhuriyet Medical Journal, 2020)
Objective: Acute appendicitis management delays results in perforation and increases the morbidity and mortality. Studies have reported a 20% perforation rate, and 2-30% negative laparotomy whose diagnoses are made by symptoms and physical examination. By using anamnesis, clinical signs-symptoms and inflammatory parameters to reduce the diagnosis time, complications, and morbidity-mortality of AA, various scoring methods have been developed. The first scoring system defined for this purpose is Alvarado scoring system. The RIPASA scoring system was developed for patients in Asia. In this study, we aimed to determine which scoring is more suitable for our population by comparing Alvarado and RIPASA scoring methods in patients who underwent an appendectomy.Method: The Alvarado and RIPASA scores of each patient were calculated by the scoring system parameters after the 182 patient files were analyzed retrospectively. At cut-off value of 7.5 for RIPASA score and 7 for Alvarado score, patients were divided into high and low-risk groups. The positive predictive value, negative predictive value, sensitivity, and specificity were calculated and the two scoring systems' effectivity were compared with Chi-square and area under curve analysis.Results: According to the histological examination 42(23%) patients were not considered as acute appendicitis. RİPASA scoring systems high-risk group classification was better by predicting the acute appendicitis patients (p = 0.001, p <0.05). The area under the curve for RIPASA score calculated as 0.738 and this is statistically significant (p = 0.001; p <0.05). The result was better then the Alvarado AUC score (0,633). Alvarado scoring systems' negative predictive value was higher than the RİPASA score, respectively (58,14%, 32.56%).Conclusions: It is beneficial to use the RIPASA scoring system for patients in our region to reduce the rate of negative laparotomy and unnecessary surgical procedures in patients admitted to emergency services with the suspicion of acute appendicitis.

[No abstract available]
Keywords: acute appendicitis|RİPASA SCORE|ALVARADO SCORE; Health Care Administration; acute appendicitis; acute appendicitis; RİPASA SCORE; ALVARADO SCORE; Sağlık Kurumları Yönetimi; RİPASA SCORE; ALVARADO SCORE; 3. Good health